1993
DOI: 10.1111/j.1360-0443.1993.tb02056.x
|View full text |Cite
|
Sign up to set email alerts
|

The origin of alcohol‐related social norms in the Saami minority

Abstract: The present paper addressed the problem of the origin of alcohol-related social norms in the Saami minority in northern Norway. Based on data from studies of comparable ethnic minorities in Greenland, North America and Australia it could be expected that alcohol use- and abuse would be more prevalent in the Saami than in the Norwegian populations of northern Norway. No data to support this hypothesis exist. On the contrary, available data suggest that drinking problems in this group are similar to those of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…This assumption was partly based on data on drinking behaviour found in comparable minorities. There is, however, no data to support this hypothesis (13). In line with this, we found the proportion of frequent drinkers (two or more times a week) to be 11% in the non-Sámi, compared to 6% in the Sámi populations (data not shown).…”
Section: Discussionsupporting
confidence: 50%
“…This assumption was partly based on data on drinking behaviour found in comparable minorities. There is, however, no data to support this hypothesis (13). In line with this, we found the proportion of frequent drinkers (two or more times a week) to be 11% in the non-Sámi, compared to 6% in the Sámi populations (data not shown).…”
Section: Discussionsupporting
confidence: 50%
“…According to the relatively few studies on the health situation among the Sami population, there is so far no evidence of a more disadvantaged health status. Compared to the majority population, studies have shown less alcohol use among Sami adults and adolescents (21)(22)(23) and similar rates of mental health problems, smoking and sexual risktaking behaviour for adolescents (22,24,5). This pattern differs with that for several other Indigenous populations worldwide.…”
Section: What Can Explain the Moderate Rates Of Suicidal Behaviour Ammentioning
confidence: 48%
“…Some studies based on the cardiovascular screening reports in Finnmark County have shown only minor differences in risk factors (3)(4)(5)(6)(7)(8), and they applied a definition of Sámi ethnicity based on a person having at least two Sámi-speaking grandparents. Other studies have focused on alcohol consumption (9,10). In addition, there exist many publications on health and ethnicity among school children and adolescents (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%